Ujaran Kebencian Terhadap Gus Ulil pada Debat Pertambangan Raja Ampat dalam Tiktok Rosi_KompasTV: Hate Speech Against Gus Ulil in the Raja Ampat Mining Debate on Tiktok Rosi_KompasTV - Nuriya Lutfi Apriliani; Yeni Puspitasari; Nur Lailiyah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to describe the forms of hate speech found in the comment section of the Rosi Kompas TV TikTok account, specifically on an uploaded video featuring a debate on mining activities in Raja Ampat directed at Gus Ulil Absor Abdalla, employing a forensic linguistic framework as the analytical lens. This study adopts a qualitative descriptive method, with primary data consisting of 55 user comments collected through documentation techniques. The analysis was conducted by examining linguistic aspects including diction, sentence structure, meaning, and utterance context, while cross-referencing the findings with legal regulations stipulated in the Electronic Information and Transactions Law (UU ITE). The results identified three categories of hate speech, namely insult (32 instances), defamation (13 instances), and ethnicity-, religion-, race-, and intergroup-based hate speech known as SARA (10 instances). Linguistically, these utterances were characterized by the use of pejorative lexicon, negative labeling of individual identity, degrading metaphors, and nonverbal symbols that reinforce the intent to attack. These findings affirm the critical role of forensic linguistic analysis in identifying and substantiating hate speech in the digital sphere as part of law enforcement efforts.